2007
DOI: 10.1108/01425450710719987
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and impact of flexible working arrangements in smaller businesses

Abstract: Emerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series volumes, as well as providing an extensive range of online products and additional customer resources and services. Emerald is both COUNTER 4 and TRANSFER compliant. The organization is a partner of the Committee on Publication Ethics (COPE) and also works with Portico and the LOCKSS initiative for digital archive preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 48 publications
2
73
0
1
Order By: Relevance
“…Previous research has concluded how flexible working arrangements in an organization would influence organizational commitment, and generally found a positive relationship between these two variables (Grover & Crocker, 1995;Thompson et al, 1999;Dex & Smith, 2002;Harris & Foster, 2005;Maxwell et al, 2007). There is continuous interest from other researchers to study flexible work as it has been advocated as a means of increasing organizational commitment.…”
Section: Relationship Between Flexible Working Arrangement and Organimentioning
confidence: 99%
“…Previous research has concluded how flexible working arrangements in an organization would influence organizational commitment, and generally found a positive relationship between these two variables (Grover & Crocker, 1995;Thompson et al, 1999;Dex & Smith, 2002;Harris & Foster, 2005;Maxwell et al, 2007). There is continuous interest from other researchers to study flexible work as it has been advocated as a means of increasing organizational commitment.…”
Section: Relationship Between Flexible Working Arrangement and Organimentioning
confidence: 99%
“…Maxwell et al . (: 138) suggest FWAs for worker benefit comprise ‘any policies and practices, formal or informal, which permit people to vary when and where work is carried out’. This combines type of FWAs with formality of their offer, one of the few definitions to consider the nature of formality, and we develop this definition below.…”
Section: Flexible Workingmentioning
confidence: 97%
“…We sound, however, a note of caution. While idiosyncratic approaches, both formal and informal, may play to such strengths in responding to older workers' need for FWAs, lack of transparent policy may also permit managers to resist worker‐oriented FWAs and detract from worker awareness of their options (Maxwell et al ., ). Rousseau et al .…”
Section: Flexible Workingmentioning
confidence: 99%
“…According to results of research whose sample is human resources directors of 85 organizations which work in telecommunication, finance, and technology sector in South Africa, the most significant advantages of flexible working arrangements are respectively job satisfaction, productivity, using time and work-family balance (Grobler and Bruyn, http://dx.doi.org/10.15405/epsbs.2017.12.02.19 Corresponding Author: Özlem Çetinkaya Bozkurt Selection and peer-review under ). Also a survey shows that flexible working arrangements which are used by small sized enterprise in Scotland lead lots of benefits in catching and keeping employee, improvement the managementemployee relationship and increasing job commitment (Maxwell, & Rankine, 2007). In the research conducted with 100 people, Jain and Swami (2014) defend that flexible working is a good policy in order to keep qualified employees in the organization for growing economies and competitive markets.…”
Section: Flexible Working Subjective Well-being and Intention To Leavementioning
confidence: 99%
“…The studies about flexible working are generally related with job satisfaction, organizational commitment, work-family conflict, work-family balance, absenteeism and performance (Kim and Campagna, 1981;Choo et. al., 2016;Grover and Crocker, 1995;Thompson et al, 1999;Harris and Foster, 2005;Maxwell, & Rankine, 2007). Because the flexible working makes easy to balance between work and family roles, it is expected that individuals feel better and dedicate himself or herself to work with higher energy.…”
Section: Flexible Working Subjective Well-being and Intention To Leavementioning
confidence: 99%